Performance-enhancing effects of caffeine and L-Theanine among Iranian elite wrestlers: a focus on cognitive and specific physical performance - Razazan, R.; Hemmatinafar, M.; Imanian, B.; Jahaniboushehri, N.; Rezaei, R.; Nazemzadegan, G. (Journal of the International Society of Sports Nutrition, 2025)
Background Caffeine is a well-known ergogenic aid that can enhance physical and cognitive performance. However, it often induces side effects, such as anxiety and overstimulation, which can be problematic in high-pressure sports like wrestling. L-theanine, a non-stimulant amino acid found in tea, may help mitigate these effects by promoting a calm yet focused mental state. This study aimed to investigate the acute effects of caffeine, L-theanine, and their combination on physical performance, cognitive function, and anxiety in elite male wrestlers.